The role of print sports media in reducing violence in football clubs in Al Mahwit Governorate, Republic of Yemen - A study focused on the Yemeni Sport newspaper - - hocine nacer al sofi, bakil (sports creativity, 2025)
Our current study aims to identify the role of print sports media in reducing or mitigating the widespread phenomenon of violence among athletes in Al Mahwit Governorate clubs, particularly in football, given its popularity and large fan base. The descriptive approach was used as it was best suited to the nature of the study. The sample consisted of (15) sports clubs based in Al Mahwit Governorate that are officially recognized by the Ministry of Youth and Sports and registered with the Yemeni Football Association. The results showed the following: 1. 64.28% of the target sample follow sports news through the Yemeni Sport newspaper. 2. 53.57% of the sample supported the Yemeni Sport newspaper's neutrality and objectivity in reporting sports information and events. 3. 71.42% of the sample agreed that the newspaper reports news according to the demands of the Yemeni sports community. 4. 67.85% of the sample supported the opinion that Yemen Sport maintains its neutral stance and reports news without supporting or opposing any particular party or team. 5. 61.78% of the study sample confirmed that the newspaper does not contribute to creating conflicts and unrest in the sports community. 6. 82.14% of the sample responded that Yemen Sport reports news without distortion or falsification. 7. 71.43% of the sample believe that certain sections of Yemen Sport contribute to reducing the phenomenon of sports violence. 8. 71.42% of the sample believe that the type of news published by Yemen Sport significantly contributes to reducing the phenomenon of sports violence. 9. A very large percentage (89.29%) of the sample agree with what Yemen Sport does. The types of content used by readers are insufficient and do not meet the demand. 10. A percentage (85.72%) of the respondents believe that the Yemeni Sport newspaper strives to educate its sports audience through various means.